Saudi Vision 2030: Public Diplomacy Efforts Through Transfer of Top European Football Players to the Saudi Arabian League - Indra Tamsyah; Sohyb , Muh Nizar; Manggarsari, Yuniarsih (Papua Journal of Diplomacy and International Relations, 2025)
Saudi Arabia is striving to reduce its dependence on state revenue derived from oil. In this effort, Saudi Arabia formulated Vision 2030, which serves as the framework for their economic reforms. This research aims to elaborate on Saudi Arabia's public diplomacy efforts to introduce their economic transformation plan. To obtain accurate answers, this research employs public diplomacy theory using a qualitative descriptive method along with secondary data sources. The research findings indicate that Saudi Arabia conducts public diplomacy in three ways. First, the management of news related to Vision 2030 is carried out by an agency called the Saudi Press Agency (SPA), which is owned by the Saudi government. Second, creating an official website and social media for Vision 2030 that contains comprehensive information related to Vision 2030 so that it can be accessed by the general public. Then, Saudi Arabia will also host the Great Future Initiative Campaign, which will begin in May 2024 and is planned to last for 12 months, with the main goal of fostering a strong partnership between Saudi Arabia and the UK in the fields of economy and development, as well as potential sectors. Third, Saudi Arabia is building good relationships with important and influential actors, in this case, the top European players who have moved to the Saudi Pro League. Players like Cristiano Ronaldo are a major attraction that helps promote Saudi Arabia in general, as well as several tourism projects being undertaken by Saudi Arabia as part of Vision 2030. KEYWORDS Public Diplomacy; Saudi Arabia; Vision 2030.